Water‐Soluble Polymeric Carbon Nitride Colloidal Nanoparticles for Highly Selective Quasi‐Homogeneous Photocatalysis. (26th November 2019) - Krivtsov, Igor; Mitoraj, Dariusz; Adler, Christiane; Ilkaeva, Marina; Sardo, Mariana; Mafra, Luís; Neumann, Christof; Turchanin, Andrey; Li, Chunyu; Dietzek, Benjamin; Leiter, Robert; Biskupek, Johannes; et al.
Abstract: Heptazine‐based polymeric carbon nitrides (PCN) are promising photocatalysts for light‐driven redox transformations. However, their activity is hampered by low surface area resulting in low concentration of accessible active sites. Herein, we report a bottom‐up preparation of PCN nanoparticles with a narrow size distribution (ca. 10±3 nm), which are fully soluble in water showing no gelation or precipitation over several months. They allow photocatalysis to be carried out under quasi‐homogeneous conditions. The superior performance of water‐soluble PCN, compared to conventional solid PCN, is shown in photocatalytic H2 O2 production via reduction of oxygen accompanied by highly selective photooxidation of 4‐methoxybenzyl alcohol and benzyl alcohol or lignocellulose‐derived feedstock (ethanol, glycerol, glucose). The dissolved photocatalyst can be easily recovered and re‐dissolved by simple modulation of the ionic strength of the medium, without any loss of activity and selectivity. Abstract : Quasi‐Modus : Wasserlösliche kolloidale Nanopartikel aus polymerem Kohlenstoffnitrid ermöglichen eine quasi‐homogene Photokatalyse mit außergewöhnlicher Aktivität. Der gelöste Photokatalysator kann durch einfache Modulation der Ionenstärke des Mediums leicht zurückgewonnen und wieder aufgelöst werden, wobei seine Aktivität und Selektivität erhalten bleiben.